(untitled) (Research, Society and Development, 2020)
Objective: This paper aims to evaluate birth weight and maternal nutritional status in children’s body composition aging from 7 to 9 years old. Methods: Transversal study composed of collecting interviewee’s socio economic and anthropometrical variables in which 41 children and their mothers were evaluated in the city of Picos in Piaui state. The following mother’s anthropometrical parameters were investigated: weight, height, and waist circumference. In addition, the following student’s anthropometrical variables were collected: born and current weight, height, waist circumference (WC), arm circumference (AC), subscapular skinfold (SS), and triceps skinfold (TS). Results: Birth weight relates positively and significantly with some anthropometrical variables of children, such as: waist circumference (WC; p=0.02), arm circumference (AC; p=0.03), subscapular skinfold (SS; p=0.02), and percentage of body fat (%BF; p=0.05). A statistically positive correlation between children’s current weight and mother’s current weight (p=0,04) was observed. Besides, a lower, but more significant inverse correlation between mother’s height and variables referring to children’s body composition was found. Conclusion: The following paper suggests that born weight correlates with children’s current bodily composition and that, no matter what the born weight is, mother’s weight is relevant to the children’s current weight, demonstrating the importance of continuous screening of nutritional status between mother and children.